4-Sodium phenyl butyric acid has both efficacy and counter-indicative effects in the treatment of Col4a1 disease. (22nd October 2018) - Jones, Frances E; Murray, Lydia S; McNeilly, Sarah; Dean, Afshan; Aman, Alisha; Lu, Yinhui; Nikolova, Nija; Malomgré, Ruben; Horsburgh, Karen; Holmes, William M; Kadler, Karl E; Van Agtmael, Tom
Abstract: Mutations in the collagen genes COL4A1 and COL4A2 cause Mendelian eye, kidney and cerebrovascular disease including intracerebral haemorrhage (ICH), and common collagen IV variants are a risk factor for sporadic ICH. COL4A1 and COL4A2 mutations cause endoplasmic reticulum (ER) stress and basement membrane (BM) defects, and recent data suggest an association of ER stress with ICH due to a COL4A2 mutation. However, the potential of ER stress as a therapeutic target for the multi-systemic COL4A1 pathologies remains unclear. We performed a preventative oral treatment of Col4a1 mutant mice with the chemical chaperone phenyl butyric acid (PBA), which reduced adult ICH. Importantly, treatment of adult mice with the established disease also reduced ICH. However, PBA treatment did not alter eye and kidney defects, establishing tissue-specific outcomes of targeting Col4a1-derived ER stress, and therefore this treatment may not be applicable for patients with eye and renal disease. While PBA treatment reduced ER stress and increased collagen IV incorporation into BMs, the persistence of defects in BM structure and reduced ability of the BM to withstand mechanical stress indicate that PBA may be counter-indicative for pathologies caused by matrix defects. These data establish that treatment for COL4A1 disease requires a multipronged treatment approach that restores both ER homeostasis and matrix defects. Alleviating ER stress is a valid therapeutic target for preventing and treating established adult ICH, but collagen IV patients will require stratification based on their clinical presentation and mechanism of their mutations.